Inverse synthetic aperture radar-based covert system for human identification - GEREN, WILLIAM P; MORGAN, DOUGLAS P (2004)
The method involves gathering surface data of a subject using inverse synthetic aperture radar. A source signal is directed by the radar towards the subject when the subject is rotated through a range of motion. A returned signal is collected and transformed into a quantitative representation of the data. The representation is added to or checked against the archive to determine if a human target is indexed in the archive. Independent claims are also included for the following: (a) a method for identifying a subject indexed in an archive of previously catalogued subjects; (b) an apparatus for creating a quantitative representation of a surface of a subject; (c) a computer readable medium for generating a quantitative, three-dimensional representation of a subject; and (d) a computer readable medium for identifying a subject indexed in an archive of previously catalogued subjects.